Role of Ca2+/calmodulin and PI3K/AKT signaling pathways and active ingredients of BaoTaiYin in treatment of recurrent miscarriage - Ji, Li; Deng, Anqi; Chen, Huiying; Guo, Shuangyan; Wang, Pingyu; Zhang, Ruiyi; Chen, Wenyang; Fan, Taotao; Jiang, Lijuan; Shen, Bing (Frontiers in Molecular Biosciences, 2025)
IntroductionBaoTaiyin (BTY) is a traditional Chinese medicine decoction. It has been used to treat recurrent miscarriage (RM). However, there are no comprehensive systematic studies to identify the chemical compositions of BTY and molecular mechanisms on RM. Finding the chemical components of BTY and clarifying the underlying processes in the treatment of RM were the goals of the study.MethodsWe used ultra-high-performance liquid chromatography coupled with triple quadruple time-of-flight tandem mass spectrometry to analyze the chemical components of BTY, network analysis to predict the pharmacological effects of the identified active ingredients, and cell experiments to identify potential molecular mechanisms.ResultsWe found 12 active ingredients among 61 components identified in BTY. These identified activities were linked to regulatory effects on 127 key signaling pathways, targeting 107 proteins. Through network analysis, we determined that insulin-like growth factor 1 receptor, matrix metalloproteinases, PI3K, and STAT3 may be the core targets of BTY’s therapeutic effects on RM. We further explored this mechanism to find that aqueous extracts of BTY significantly enhanced IGFBP2 and CaMKK2 expression and trophoblast proliferation, whereas inhibitors of IGF1R/PI3K/AKT pathway or CaMKK2 blocked the effect of BTY on trophoblast proliferation. In addition, IGFBP2 siRNA suppressed BTY-induced CaMKK2 expression. Caffeic acid, as one of components of BTY, increased intracellular Ca2+ concentration and proliferation in trophoblast.ConclusionOur research showed that BTY may have therapeutic benefits on RM through multiple targets and pathways, such as the IGF1R/PI3K/AKT and Ca2+/calmodulin signaling pathways.